Olympics: Improving the Competition Strategy in Each Skill Technique of Elite Swimmers for the 400 meters Freestyle - Waristra Tyo Nirwansyah; Bayu Agung Pramono; Gigih Siantoro; Muhammad; I Dewa Made Aryananda Wijaya Kusuma; Muhammad Kharis Fajar; Mohamad Rozi bin Yacob (Physical Education Theory and Methodology)
Background. In swimming championships, strategy setting is considered to be the main factor, especially in the middle and long-distance events. Implementing a strategic change can indirectly affect the final results.